2006
DOI: 10.1590/s1516-31802006000200008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single dose of dexamethasone on patients with systemic inflammatory response

Abstract: CONTEXT AND OBJECTIVE: Systemic inflammatory response syndrome (SIRS) is a very common condition among critically ill patients. SIRS, sepsis, septic shock and multiple organ dysfunction syndrome (MODS) can lead to death. Our aim was to investigate the efficacy of a single dose of dexamethasone for blocking the progression of systemic inflammatory response syndrome. DESIGN AND SETTING: Prospective, randomized, double-blind, single-center study in a postoperative intensive care unit (Surgical Support Unit) at Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
(54 reference statements)
1
13
0
Order By: Relevance
“…If inadequate secretion of CCT fails to suppress inflammation, hormonal administration should promote GC antiinflammatory function by decreasing the production of inflammatory cytokines, cytokine-driven HPA axis activity and cytokine-driven organ dysfunction (Meduri 1999). The effects of dex are repeatedly demonstrated, and the results of the present study are in agreement with the literature regarding the prevention of lung inflammation (Meduri et al 2002;Wang et al 2008), oxidative stress and MPO activity (Sun et al 2009), decreased alveolar collapsed area and improvement in the physiological parameters of respiratory mechanics (Meduri et al 2002;Rocco et al 2003) with a consequent increase in survival (Cicarelli et al 2006(Cicarelli et al , 2007.…”
Section: Discussionsupporting
confidence: 92%
“…If inadequate secretion of CCT fails to suppress inflammation, hormonal administration should promote GC antiinflammatory function by decreasing the production of inflammatory cytokines, cytokine-driven HPA axis activity and cytokine-driven organ dysfunction (Meduri 1999). The effects of dex are repeatedly demonstrated, and the results of the present study are in agreement with the literature regarding the prevention of lung inflammation (Meduri et al 2002;Wang et al 2008), oxidative stress and MPO activity (Sun et al 2009), decreased alveolar collapsed area and improvement in the physiological parameters of respiratory mechanics (Meduri et al 2002;Rocco et al 2003) with a consequent increase in survival (Cicarelli et al 2006(Cicarelli et al , 2007.…”
Section: Discussionsupporting
confidence: 92%
“…24,25 The reduction of collagen synthesis demonstrated a potential negative effect of this drug in tissue repair. These findings were identified after an ultrastructural study performed on days 3 and 5 after use of dexamethasone, when fibroblasts exhibited few organelles and a reduced collagenous matrix.…”
Section: Marchionni Et Almentioning
confidence: 99%
“…As an anti‐inflammatory drug, DEX is known to control the endotoxin‐induced lung inflammation and inflammatory cytokines . Clinical trial studies have shown the beneficial role of DEX in septic shock or systemic inflammatory condition . Moreover, DEX is often given to cancer patients before or after chemotherapy to control acute nausea and pain .…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Clinical trial studies have shown the beneficial role of DEX in septic shock or systemic inflammatory condition. 40,41 Moreover, DEX is often given to cancer patients before or after chemotherapy to control acute nausea and pain. 42 Importantly, low dose of DEX is also used as a palliative therapy in castration-resistant PCa treatment.…”
mentioning
confidence: 99%